Multithreading in C♯ 5.0 cookbook : over 70 recipes to help you learn asynchronous and parallel programming with C♯ 5.0 quickly and efficiently /: over 70 recipes to help you learn asynchronous and parallel programming with C♯ 5.0 quickly and efficiently. (2013) - Unknown
No abstract available